Answer:
-10.25
Step-by-step explanation:
Answer:
(6,3)
Step-by-step explanation:
y=2/3 x - 1
y=-1/2 x + 6
Since both equations are equal to y, we can set them equal
2/3 x - 1 =-1/2 x + 6
We have fractions, so I will multiply by 6 to clear the fractions
6(2/3 x - 1) =(-1/2 x + 6)6
Distribute
4x -6 = -3x +36
Add 3x to each side
4x+3x -6 = -3x+3x +36
7x -6 = 36
Add 6 to each side
7x-6+6 = 36+6
7x = 42
Divide each side by 7
7x/7 = 42/7
x =6
Now we need to find y
y =2/3x -1
y = 2/3(6) -1
y = 4-1
y=3
(6,3)
Answer:2.8
Step-by-step explanation:add 3.5 to the 10.5 which equals 14 then you divide 5 by 14 to get the y alone and it equals 2.8